2010
DOI: 10.1111/j.1365-2591.2009.01651.x
|View full text |Cite
|
Sign up to set email alerts
|

A metallurgical characterization of ten endodontic Ni‐Ti instruments: assessing the clinical relevance of shape memory and superelastic properties of Ni‐Ti endodontic instruments

Abstract: The endodontic instruments tested were manufactured from cold worked Ni-Ti wires and thus have neither shape memory nor superelastic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 40 publications
3
95
0
16
Order By: Relevance
“…HyFlex instruments made from CM Wire were commercialized in 2011. They exhibit a lower percent in weight of nickel (52 Ni %wt) than the common 54.5-57 Ni %wt of the great majority of commercially available SE NiTi rotary instruments (101). The recommended rotational speed is 500 rpm with a torque setting of up to 2.5 N/cm (www.…”
Section: Hyflex and Typhoon CM Instrumentsmentioning
confidence: 99%
“…HyFlex instruments made from CM Wire were commercialized in 2011. They exhibit a lower percent in weight of nickel (52 Ni %wt) than the common 54.5-57 Ni %wt of the great majority of commercially available SE NiTi rotary instruments (101). The recommended rotational speed is 500 rpm with a torque setting of up to 2.5 N/cm (www.…”
Section: Hyflex and Typhoon CM Instrumentsmentioning
confidence: 99%
“…The EDX allows to determine the composition and distribution of chemical elements in different materials and has been increasingly used in endodontics. 12,14,15,23 In our sample, the presence of chemical elements was relatively low. One explanation for this could be that only the distal canals of mandibular molars were analyzed, and these canals are usually wide and proximally Graph 1: Chemical characterization of metallic fragments found on the surface of the dentinal walls of root canals in the K-FlexoFile groups 24 Previous studies 25,26 had already reported that endodontic instruments usually do not touch all dentinal walls of wide, flattened canals during the shaping process.…”
Section: Discussionmentioning
confidence: 99%
“…Zinelis et al 15 observed that the elemental composition of most NiTi instruments ranged from 54.5 to 57% for nickel weight, which is within limits established for NiTi alloys used for medical applications. 17 The defects found in the instruments used in this study are probably due to fabrication defects that are inherent to NiTi 17 and stainless steel files.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Durante esse processo, não deve ocorrer nenhuma transformação de fase e o resfriamento não pode ser induzido. Zinelis et al (2010) demonstraram que a superelasticidade (SE) das ligas de NiTi é perdida se essas não forem submetidas a um tratamento térmico adequado.…”
Section: Tratamentos Térmicos Das Ligas De Nitiunclassified